Experimental assessment of a pilot scale hybrid cooling system for water consumption reduction in CSP plants - Palenzuela, Patricia; Roca, Lidia; Asfand, Faisal; Patchigolla, Kumar (Elsevier, 2021)
The new challenge of the European Commission is to limit water consumption in Concentrating Solar Power (CSP) plants, especially significant in the cooling process. Hybrid cooling systems are presented as a potential solution to achieve water consumption reduction since they also avoid a high penalty of efficiency loss in the power block. In this work, a hybrid cooling pilot plant installed at Plataforma Solar de Almería is evaluated experimentally. The system has been tested under different ambient and operating conditions to analyze their influence on the water and electricity consumption. The results reveal that significant water savings were achieved in comparison with the conventional only-wet configuration. Concretely, a maximum water consumption saving of 67% was found at high ambient temperatures (between 25 and 30 °C) and for a thermal load of 80% when a hybrid configuration was used. The optimal operating strategies that achieve a tradeoff between low water and electricity consumption have been identified by two efficiency indexes: the specific electricity and water consumption. The parallel configuration was the optimal one in most of the cases. At high ambient temperatures and 80% thermal load, the electricity and water consumptions of this configuration were 0.033 kWe/kWth and 0.071 L/kWth, respectively.
Keywords: Hybrid cooling; Pilot plant; Water consumption saving; Experimental characterization; Optimal operating strategies